Fully Automated Laboratories and Methods. - Nietupski, Val (Education, 1965)
This article discusses present applications of automated teaching procedures and possible future applications in terms of a specific system. The amount of time allotted for the student's response is variable and is determined by the time duration of control signal placed on the program tape. Normal video is quite impractical for extensive use with multi-purpose retrieval systems since there is no practical means for storing the video signal on relatively inexpensive tape transports. The school system, thus, has the advantage of being able to select any one of more than 100 programs for lessons to enable the students to proceed at their own pace and to integrate the basic educational philosophies of the entire school system.